Detection of DENV-2 and ZIKV coinfection in southeastern Brazil by serum and urine testing - da Conceição, Pâmela Jóyce Previdelli [UNESP]; de Carvalho, Lucas Rodrigues [UNESP]; de Godoy, Bianca Lara Venâncio; Nogueira, Mauricio Lacerda; Terzian, Ana Carolina Bernardes; de Godoy, Moacir Fernandes; Calmon, Marília Freitas [UNESP]; Bittar, Cintia [UNESP]; Rahal, Paula [UNESP] (Springer Nature, 2023)
Purpose: Aedes aegypti mosquito-borne diseases have a significant impact on public health in Brazil. In this study, we investigated the presence of the Zika virus (ZIKV) and dengue virus (DENV) in serum and urine samples from symptomatic participants who attended an Emergency Care Unit located in a city in the northwestern region of São Paulo between February 2018 and April 2019. Methods: Serum and urine samples were collected from participants suspected of having arbovirus infection. After the extraction of viral RNA, viral detection was performed by real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) (One-Step RT-qPCR). Results: A total of 305 participants participated in this study. A total of 283 blood and 270 urine samples were collected. Of 305 patients, 36.4% (111/305) were positive for ZIKV, 43.3% (132/305) for DENV2, and 0.3% (1/305) for DENV1. Coinfection with ZIKV/DENV2 was observed in 13.1% of participants. If only serum samples were used, ZIKV detection would have decreased to 23.3% (71/305). Of all the participants included in the study, only one was suspected of having ZIKV infection based on clinical diagnosis, and the remaining participants were suspected of having DENV. Conclusion: By testing serum and urine samples, we increased the detection of both viruses and detected considerable levels of ZIKV and DENV-2 coinfection when compared to other studies. Additionally, we detected an unnoticed ZIKV outbreak in the city. These findings highlight the importance of the molecular diagnosis of arboviruses to aid public health surveillance and management strategies.
Keywords: Brazil; Coinfection; Dengue virus; Symptomatic infection; Urine; Zika virus